Benefits, harms and cost-effectiveness of cancer screening in Australia: an overview of modelling estimates - Jie-Bin Lew; Eleonora Feletto; Stephen Wade; Michael Caruana; Yoon-Jung Kang; Carolyn Nickson; Kate T Simms; Pietro Procopio; Natalie Taylor; Joachim Worthington; David Smith; Karen Canfell (Sax Institute, 2019)
Introduction: There are three government-funded population-based screening programs in Australia - the national breast cancer screening program (BreastScreen Australia), the National Cervical Screening Program (NCSP), and the National Bowel Cancer Screening Program (NBCSP). Options for early detection of other cancers (e.g. hepatocellular carcinoma and melanoma) are under investigation. This study provides an overview of the health benefits, harms and cost-effectiveness of population-level breast, cervical and colorectal cancer screening, targeted-risk screening for lung cancer and Lynch syndrome, and prostate specific antigen (PSA) testing in Australia. Methods: The study reviewed and, where possible, updated the estimated health benefits, harms and cost-effectiveness of screening approaches from modelling studies for four cancer types, PSA testing and Lynch syndrome testing in Australia. Costs are presented in 2018 Australian dollars. Results: The renewed NCSP (for women not HPV-vaccinated) and the NBCSP were estimated to be cost-effective versus no screening; the cost-effectiveness ratio (CER) was $16 632 per life-year saved (LYS) for the NCSP, and $3380/LYS for the NBCSP. BreastScreen Australia was predicted to have a CER of $40 279/LYS-$65 065/LYS. In 2017, the NCSP transitioned to 5-yearly primary HPV testing with partial genotyping for HPV types 16 and 18 for women aged 25-74 years. Alongside vaccination, this change is predicted to prevent a further 587 cervical cancer deaths in 2018-2035, and have a favourable benefit-to-harm balance versus prior practice (biennial cytology testing for women aged 18-69 years). On average, the NBCSP (biennial screening using an immunochemical faecal occult blood test for people aged 50-74 years) is estimated to prevent 2519 colorectal cancer deaths and result in 350 colonoscopy-related adverse events annually. The inaccuracy of PSA testing as a screening tool impedes the capacity to conduct meaningful cost-effectiveness analyses at a population level, based on current evidence. Three annual low-dose computed tomography screens for lung cancer using the US National Lung Screening Trial selection criteria would not be cost-effective in Australia. A comprehensive cost-effectiveness evaluation of systematic proband testing, cascade testing and subsequent surveillance for Lynch syndrome in Australia is currently underway. Conclusions: Current evidence supports a favourable cost-effectiveness and benefit-to-harm balance for the NCSP and NBCSP. An updated cost-effectiveness and benefits-to-harms analysis for BreastScreen Australia is required. Carefully founded quantitative estimates of health benefits, harms and cost-effectiveness provide an important aid to policy decision making, and form the basis for developing decision aids to guide individual screening decisions. Opportunities exist for lung cancer screening, systematic Lynch syndrome testing and informed decision making about PSA testing. However, more evidence is required on risk assessment, targeting of screening tests, optimal referral pathways, managing potential harms and delivering services in a cost-effective framework